Effects of pre-eclampsia/eclampsia on platelet parameters in small for gestational age preterm infants - Huang, Huiling; Zhao, Jing; Huang, Jichong; Ai, Yuan; Zhu, Tingting (Frontiers in Pediatrics, 2025)
ObjectivesTo investigate whether pre-eclampsia/eclampsia (PE/E) alters platelet parameters, including platelet count (PLT), mean platelet volume (MPV), and platelet distribution width (PDW), in small for gestational age (SGA) infants.MethodsWe enrolled 245 SGA preterm infants between 2020 and 2023. They were grouped according to their mother's PE/E status. We assessed the PLT, MPV, PDW, and prevelence of thrombocytopenia during the first 30 days after birth. Groups were compared using either χ2 test or Fisher's exact test.ResultsSGA neonates born to mothers with PE/E had a lower PLT on Day 7 than those born to mothers without PE/E (P = 0.0211). PDW and MPV values gradually increased for the first several days, and eventually stabilized around the first week. There was no statistical difference in MPV, PDW, or thrombocytopenia prevalence between SGA neonates between born to mothers with PE/E and those born to mothers without PE/E.ConclusionsEvidence to support an association between PE/E and platelets parameter in neonates is limited. SGA may be the real reason for alterations in platelet parameters in neonates.